IDENTIFIKASI KONSEP 4A DALAM POTENSI PENGEMBANGAN WISATA AIR TERJUN TIRTA BHUWANA DI DESA PEGADUNGAN, KECAMATAN SUKASADA, BULELENG - Ida Ayu Anggreni Suryaningsih (Journal of Tourism and Interdiciplinary Studies, 2023)
Tirta Bhuwana Waterfall is a natural tourist attraction in the Pegadungan Village area, Sukasada Buleleng District. This research is aimed to find out the problems which makes Tirta Bhuwana Water not well-developed. This study focused on its lack of development based on 4A potential, (Attraction, Access, Amenities and Ancillary). So far, Tirta Bhuwana Waterfall is not popular like others waterfall around. In addition, the absence of support from the government also makes this waterfall less well-known. Therefore, the purpose of this study was to analyze the potential, especially A4 in the natural tourism of Tirta Bhuwana Waterfall. The research method used is a qualitative descriptive method with data collection techniques using the observation method which focuses on analyzing the potential for developing Tirta Bhuwana Waterfall, especially in element 4A. The results of the study showed that Tirta Bhuwana Waterfall Tourism has not been optimally developed even though it has quite beautiful natural tourism potential and it is true that there is no support from the government and a lack of 4A in the development of natural tourist attractions in the form of waterfalls so that improvement or development is needed in the 4A field.